The Poetic Lexicon at Izz al-Din al-Mawsili (d.789 AH) - Fadhil Karaji, Randa; Khalaf Rewayh, Balqis (Al-Adab Journal, 2020)
The research aims to study the verbal fields that contributed to the formation of the poetry of the poet Izz al-Din al-Mawsili (d. 789 AH), who belongs to the second Mamluk era, as we took an inventory of the most common words in his poetry and their connotations through their occurrence in the context of the poetic text, and after we inventory we distributed them to semantic fields which are : (Nature's words, words of time and place, words of wine, words of color, words of love, and words of war), and these words had the effect of enriching the poetic text with the intended significance.